1977
DOI: 10.1111/j.1476-5381.1977.tb07549.x
|View full text |Cite
|
Sign up to set email alerts
|

KININ, KININOGEN AND KININASE LEVELS DURING ACUTE Babesia bovis (=B. argentina) INFECTION OF CATTLE

Abstract: 1Kinin levels began rising on day 3 after infection of cattle with Babesia bovis (=B. argentina) and attained a maximum value of 98% above preinfection levels by day 7. 2 Kininogen levels began falling on day 3 and reached minimum levels of 83% below preinfection levels on day 8. 3 Changes in both kinin and kininogen levels on day 3 coincided with the detection of low levels of parasites, and with a fall in packed cell volume. 4 Plasma kininase levels rose significantly 6 to 9 days after infection. Preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Malherbe (1956) and Maegraith et al (1957) described sludging of parasitized r.b.c.s in distended capillaries in many organs, which was a morphological aspect of the generalized shock from which the animals died. Since then several studies (Wright, 1977) have shown that vasoactive peptides (kinins) are produced in babesiosis resulting in vasodilatations and hypotensive shock. In contrast, some of the lesions in the hyperacute gerbil infection do not appear to be a consequence of vasodilatation and stagnant anoxia, but are suggestive of vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malherbe (1956) and Maegraith et al (1957) described sludging of parasitized r.b.c.s in distended capillaries in many organs, which was a morphological aspect of the generalized shock from which the animals died. Since then several studies (Wright, 1977) have shown that vasoactive peptides (kinins) are produced in babesiosis resulting in vasodilatations and hypotensive shock. In contrast, some of the lesions in the hyperacute gerbil infection do not appear to be a consequence of vasodilatation and stagnant anoxia, but are suggestive of vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some of the lesions in the hyperacute gerbil infection do not appear to be a consequence of vasodilatation and stagnant anoxia, but are suggestive of vasoconstriction. As Wright has pointed out (Wright, 1975(Wright, , 1977, the systems of coagulation, kinin metabolism and endotoxin activity are all interlinked, and the final pathophysiological picture seen in the gerbil, and indeed in other babesioses, probably depends on the particular combination resulting from these mechanisms, in conjunction with the effects of anaemia, sympathetic activation and, possibly, toxic products of parasite origin.…”
Section: Discussionmentioning
confidence: 99%